MOBILE APPLICATION FOR RESERVATION OF MEETING ROOMS AND EVENT SPACES AT MARQUEE EXECUTIVE OFFICES - Rachmaniar, Ani; Diana, Desy; Saefudin, Mohamad (Journal of Information System, Informatics and Computing, 2024)
Increasing efficiency and ease in the meeting room and event space reservationprocess is an important need for modern companies such as Marquee Executive Offices. Making a mobile application is an effective solution for managing the reservation process. Utilizing Laravel technology and the Flutter framework, this application is able to provide users with the convenience of making reservations quickly and accurately. At the development stage, the main problems faced were the complexity in integration between the backend and frontend platforms, as well as the need for a system that could handle many reservation requests simultaneously. The solution adopted involved a structured approach to development using Laravel for the backend and Flutter for the frontend, allowing the application to run smoothly and responsively. The main benefit of the application that hasbeen developed is increasing efficiency and productivity in the meeting room and event space reservation process. Users can easily view space availability, make reservations directly via mobile device, and receive instant reservation confirmation. This not only optimizes the use of space, but also improves the overall user experience, thereby strengthening the company's image as a sophisticated and efficient service provider.